The Bible in Catholic Funeral Sermons of the Seventeenth and Eighteenth Centuries in the Grand Duchy of Lithuania - Vaitkevičiūtė, Viktorija (Senoji Lietuvos literatūra, 2014)
On the basis of seventeenth-eighteenth-century sermons of Catholic funerals by various authors, the paper dwells on the interpretations of the Bible, with emphasis on the biblical images, symbols, and plots in these sermons, as well as on quotations, paraphrases, and commentaries that promoted the awareness of the notion of the world and the individual of that time. Preachers used the Bible as a source of themes, examples, and inspirations. A pericope, a quotation from the Bible at the beginning of a sermon, often serves as a structural foundation of the sermon suggesting an overall theme or a concept. The most popular in the sermons of this type are quotations from the Old Testament related to reflections on death, life, its transience, the humbleness of the human. Such specific themes of the Bible as the proximity of death, the life of the deceased in the memory of people and in his or her progeny, crying or not crying in the presence of the deceased, and almsgiving are the parts of the Bible most used for didactic purposes. Baroque preachers resorted to the Bible ingeniously, by supplementing its quotations and paraphrases with various examples from the works of antiquity authors and secular poets. The sermons of the Age of the Enlightenment show the trend of a simple, clear, and easy-to-understand elucidation of a problem. The analysis of sermons of different centuries shows that interpretation of biblical images, symbols, and plots was determined by the changes in rhetoric requirements of a particular period. The focus of Baroque writers and poets on the relations between the object, the word, and its meaning (cf. Sarbievius’s theory of conceit) had an impact on allegorical interpretation of the Bible. To move (movere) the addressee, a word or a sentence from the Bible was interpreted separately and different meanings were imparted to them, often with the help of secular or antiquity authors. Aimed at persuading the addressee, the funeral sermons of the Enlightenment sought to render the word of the Bible effective: its teachings were used as arguments, illustrations for thoughts, and counsel. In addition, interpretations of the Bible in funeral sermons of different centuries reveal the shifts in the world-view. Assisted by the Bible, Baroque preachers presented the history of the human as a manifestation of God’s will: God rewards a virtue and punishes a sin. Although this concept did not change in funeral sermons of the Enlightenment, here the individual assumed a fuller responsibility for his or her actions. Unlike the believer in Baroque sermons, the individual sought to find happiness not only in the eternal but also in the earthly world.